Revitalizing Sociological Value in The Establishment of Regional Regulations in Indonesia - Sisinaru, Sostones Yakobis (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: The determination of regional regulations is a regional right that is attributively granted by the constitution in the context of the implementation of regional government to carry out regional autonomy.Purposes of the Research: The importance of the formation of regional regulations is to accommodate sociological values.Methods of the Research: This research is normative using a statutory approach and a conceptual approach.Results Main Findings of the Research: The results of the study show that the procedure for determining regional regulations that accommodate the sociological values (living law) of a legal product must also include the tendencies and expectations of the community. Therefore, positive law will have effective force if it contains or is in harmony with the laws that live in society, so that legislation as a positive law will have effective force if it is formulated or composed based on living laws. There is a need to revise Law Number 12 of 2011 concerning the Establishment of Laws and Regulations on Content Materials, which must cover the previous sociological aspects. Finally, the resulting laws have no impact or usefulness for the community, so the legal products made are not in accordance with the needs of the community.